The Effects of the Tobacco Immunity Promotion Program in Accordance with The Family Developmental Tasks among Senior Primary School Male Students - Yaowa, Rawadee; Lapvongwatana, Punyarat; Chansatitporn, Nutkamol (Journal of The Royal Thai Army Nurses, 2023)
This research was conducted using a quasi-experimental research design, which aimed to study the effects of the tobacco immunity promotion program in accordance with the family developmental tasks among senior primary school male students. The sample included students from ages 11-12 years, and their parents. The sample was divided into 36 persons in an experimental group and 36 persons in a comparison group. The experimental group received the tobacco immunity promotion program and family developmental tasks activities. The data were collected by self–administered questionnaires. Statistics used Descriptive statistics, independent t-test, Paired t-test, and repeated measure ANOVA. The results showed that after the experiment, the experiment group had higher mean scores of knowledges about the dangers of tobacco and self-protection by staying away from tobacco, perceived parental care according to family developmental tasks including confidence in practicing family developmental tasks to promote tobacco immunity for their children after the experiment were significantly higher than the comparison group at p-value < 0.05. This program could better strengthen tobacco immunity to students, especially with the promotion of family development tasks to students and their parents, to enable students to perceive better careand build confidenee in parents to strengthen tobacco immunity to their childresn.